Penggunaan Serbuk Kaca Sebagai Subtitusi Agregat Halus untuk Meningkatkan Kuat Tekan Beton - Rio Rahma Dhana; Syamsul Arif (Jurnal Manajemen Teknologi & Teknik Sipil, 2021)
A large amount of waste is generated from various industrial activities. Limah glass is one of the wastes that allows it to be used as an alternative solution to environmental problems. This study aims to determine the effect of the use of glass waste on the compressive strength of concrete. The experimental method was applied by mixing glass waste which was made into powder with a percentage of 0%, 5%, 15%, and 25% as a fine aggregate substitute. The quality of the concrete is planned to be Fc'16.6 with 12 samples of cylindrical 15x30 cm. The compressive strength test was carried out at the age of 7 and 28 days of concrete. The results showed that there was a decrease in each variation of the mixture. In testing the compressive strength of concrete aged 7 days, the highest compressive strength was obtained in concrete with the addition of glass powder with a percentage of 5% with a compressive strength value of 23.97 Mpa. While at the age of 28 days, the highest compressive strength was obtained in concrete with the addition of glass powder with a percentage of 5% with a compressive strength value of 34.24 Mpa.